Promoting Organizational Citizenship Behavior among Employees - The Role of Leadership Practices - Rajiani, Ismi (Canadian Center of Science and Education, 2013)
Despite of numerous studies that investigate the relationship between leadership and The Organizational Citizenship Behavior, very few of these studies have examined the influences of leadership practices – as defined by Kouzes and Posner (1987) - on organizational citizenship behaviors. Moreover, most of these studies have been conducted in western context (developed counties). In this regard, current study has three main purposes: first, investigate the influences of leadership practices on organizational citizenship behaviors. Second, conduct this investigation in Arabic context (developing country). The third purpose of this study is to investigate the mediating effect of organizational commitment on the relationship between leadership practices and organizational citizenship behaviors. Using the response of 108 non managerial banks employees, the result indicated that leadership practices have a significant positive impact in the organizational commitment and OCB. The results of the study found that organizational commitment does partially mediate the relationship between leadership practices and Organizational Citizenship Behavior. Keywords: leadership practices, organizational citizenship behavior, organizational commitment, Yemen